HYDROGEOCHEMICAL ASPECTS IN COASTAL AQUIFERS - A CASE STUDY FROM CUDDALORE DISTRICT, SOUTH INDIA: Life Science-Environmental sciences - SENTHILKUMAR G; RAMANATHAN AL; NAINWAL HC (International Journal of Life Science and Pharma Research, 2012)
This paper examines the hydrogeochemical processes due to the over exploitation of groundwater, which results in decline of water levels, leading to intrusion of salt water along the coastal region of the Cuddalore District, Tamilnadu, South India. Major cations and anions (pH, EC, TDS, Ca+ , Mg+ , Na+ , K+ , Cl- , HCO3 - , H4SiO4, F- , SO4 and NO3 - ) were analyzed for 54 groundwater samples collected in two seasons, post monsoon and pre monsoon of 2007. The groundwater chemistry commonly found to be mixed with sea water composition. Interpretation of analyzed data showed that cations were mainly contributed by natural weathering process and NO3, F- and PO4 were contributed from anthropogenic sources. Na+ – Cl- , Ca+ - Cland Mg+ – Cl- were the dominant water facies in the study area. Water quality shows that increase of ionic strength from recharge to discharge area with few anomalous values in the central part of the Cuddalore region.